Numerical Simulation of the Erosion Effect Caused by the Impact of High-Velocity Landslide - Cheng Qiao; Youcai Chen; Xuelin Chen (Shock and Vibration)
Due to the complex composition consisting of solid particles and fluids with different physical properties, geophysical flows often show complex and diverse dynamic characteristics. For landslides with high water content, there are complex interactions between the solid and fluid phases. Therefore, it is difficult to grasp the dynamic characteristics and the disaster scale of this type of landslide, especially under complex terrain and ground conditions. The drag effect is an important aspect of the interaction between the solid and liquid phases. We optimized the enhanced drag coefficient formula to further consider the effect of high-velocity movement. By considering the volume fraction relationships between different phases, a mechanical erosion rate model is utilized for multiphase flows. Based on the r.avaflow numerical tool and the multiphase mass flow model, considering the interphase interaction characteristics of high-velocity liquefied landslides, we analyzed the influence of the obstruction of buildings and their entrainment into the landslide on the dynamic characteristics and hazard range of the Shenzhen 2015 landslide. This provides a reference for the analysis of complex geophysical disasters based on the multiphase mass flow model. Importantly, we have demonstrated the reduced mobility of the considered erosive impact event, which is in line with the physical principle.